Artificial Intelligence-Based Project-Based Learning on Critical Thinking Skills: A Quasi-Experimental Study in Elementary School - Nida Khairiyah Nur Ramadhani; Nurratri Kurnia Sari (GoAcademica Research & Publishing, 2026)
This study aims to determine the influence of the Artificial Intelligence (AI)-based Project-Based Learning (PjBL) model on grade IV students' critical thinking abilities in science subjects at SDN Gentan. This study uses a post-test only control group design. The subjects of this study consisted of two groups: an experimental class that received an AI-based PjBL learning model and a control class that received a non-AI-based PjBL learning model. The instruments used in the study included multiple-choice tests to measure critical thinking skills and validated, reliable questionnaires. Data were analyzed using an independent-samples t-test after meeting the prerequisite test. The results showed a significant difference between the experimental and control classes, with a p-value of 0.003 (< 0,05), indicating that AI-based PjBL significantly improved students' critical thinking skills.